Timeline of Translational Formulation Technologies for Cancer Therapy: Successes, Failures, and Lessons Learned Therefrom - Alexandre Pérez-López; Cristina Martín-Sabroso; Ana Isabel Torres-Suárez; Juan Aparicio-Blanco (MDPI AG, 2020)
Over the past few decades, the field of cancer therapy has seen a significant change in the way in which formulations are designed and developed, resulting in more efficient products that allow us to ultimately achieve improved drug bioavailability, efficacy, and safety. However, although many formulations have entered the market, many others have fallen by the wayside leaving the scientific community with several lessons to learn. The successes (and failures) achieved with formulations that have been approved in Europe and/or by the FDA for the three major types of cancer therapy (peptide-based therapy, chemotherapy, and radiotherapy) are reviewed herein, covering the period from the approval of the first prolonged-release system for hormonal therapy to the appearance of the first biodegradable microspheres intended for chemoembolization in 2020. In addition, those products that have entered phase III clinical trials that have been active over the last five years are summarized in order to outline future research trends and possibilities that lie ahead to develop clinically translatable formulations for cancer treatment.